Description of CuInP2S6 ferrielectrics in a mixed Ising model - R. Yevych; V. Liubachko; V. Hryts; M. Medulych; A. Kohutych; Yu. Vysochanskii (Condensed Matter Physics, 2024)
The appearance of spontaneous polarization in CuInP2S6 ferrielectrics is related to the second order Jahn-Teller effect for copper cations located in a double-well local potential, the stereoactivity of indium cations located in a three-well local potential, as well as the valence fluctuations of phosphorus cations. The paraelectric to ferrielectric phase transition is primarily determined by the coupling of indium cations with their surroundings. This transition can be analyzed using the mixed Ising model with spins s = 1/2 and S = 1. The spectrum of pseudospin fluctuations at different temperatures was calculated using a mean-field approach for a set of quantum anharmonic oscillators. The results were then compared with Raman spectroscopy data for CuInP2S6 crystal. The analysis indicates that the lattice anharmonicity below 150 K, is mainly determined by the indium sublattice, leading to the coexistence of the glassy state and ferrielectric phase. Above 150 K, the anharmonicity of the copper sublattice activates the ionic conductivity and results in the existence of a long-ranged fluctuated cluster of spontaneous polarization in a temperature interval of the paraelectric phase above TC.